PERENCANAAN SISTEM TATA UDARA GEDUNG AULA SMK NEGERI 1 SEKAYU - Andriani, Novi; Hidayati, Baiti (Universitas Tridinanti Palembang, 2018)
The planning of the air system is intended to calculate the cooling load in the Hall of SMKN 1 Sekayu. So that before the AC was installed in the SMKN 1 Sekayu had an overview of the amount of AC capacity needed to condition the air in the hall with dimensions of 18 m x 16 m x 6 m. To obtain these results, the authors used the CLTD (Cooling Load Temperature Difference) calculation method based on ASHRAE GRP 158 Cooling Load Calculation Manual. Which consists of calculation of Extenal and Internal cooling loads. Calculation of cooling load based on primary and secondary data which then results are adjusted to the type of air system. After calculating the cooling load, the maximum load results are obtained at 237013,1917 Btu / hr, thus the AC capacity needed is 26 Pk with the Direct Refrigerant System, AC Floor Standing system.